2010
DOI: 10.1155/2010/506047
|View full text |Cite
|
Sign up to set email alerts
|

From Cisplatin-Containing Sequential Radiochemotherapy towards Concurrent Treatment for Patients with Inoperable Locoregional Non-Small Cell Lung Cancer: Still Unanswered Questions

Abstract: Radiotherapy has been the mainstay of the treatment of stage III non-small cell lung cancer (NSCLC) patients. In the early nineties, combined treatment with chemotherapy was introduced. In 1995, a meta-analysis showed improved treatment outcome of the sequential use of radiochemotherapy (RCT) compared to radiotherapy alone, provided cisplatin was part of the chemotherapy course. Concurrent RCT compared to radiotherapy only yielded the same improvements of 4% in the 2-year and 2% in the 5-year overall survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…However, the risk of electrolyte abnormalities during DLD regimen should be closely monitored in daily basis during therapy so that adequate supportive care intervention can be given appropriately. Based on our findings, choice of the cisplatin dose should be based on the patients’ age, comorbidities as well as electrolyte status ( Koning et al., 2010 ). Overall, the DLD regimen leads to equal therapeutic efficacy with a lower risk profile for moderate-to-severe toxicities, indicating that the DLD regimen could improve patients’ quality of life.…”
Section: Discussionmentioning
confidence: 97%
“…However, the risk of electrolyte abnormalities during DLD regimen should be closely monitored in daily basis during therapy so that adequate supportive care intervention can be given appropriately. Based on our findings, choice of the cisplatin dose should be based on the patients’ age, comorbidities as well as electrolyte status ( Koning et al., 2010 ). Overall, the DLD regimen leads to equal therapeutic efficacy with a lower risk profile for moderate-to-severe toxicities, indicating that the DLD regimen could improve patients’ quality of life.…”
Section: Discussionmentioning
confidence: 97%
“…[9] Until the 1990's radiotherapy alone was the standard treatment for patients with inoperable NSCLC, however the 5-year survival rate was poor (under 10%). [1012] Over the last two decades, a number of studies have demonstrated that chemotherapy and radiotherapy can prolong survival and are recommended as treatment for locally advanced disease. [5,10,1315] The combination of radiotherapy plus platinum-based chemotherapy for locally advanced NSCLC shows survival benefit compared with radiation therapy alone, and is considered the current standard of care.…”
Section: Introductionmentioning
confidence: 99%
“…[1012] Over the last two decades, a number of studies have demonstrated that chemotherapy and radiotherapy can prolong survival and are recommended as treatment for locally advanced disease. [5,10,1315] The combination of radiotherapy plus platinum-based chemotherapy for locally advanced NSCLC shows survival benefit compared with radiation therapy alone, and is considered the current standard of care. [48] The median survival time for the combined therapy ranges from 12 to 14 months while radiation alone ranges from 9 to 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…Platinum chemotherapeutic drugs are commonly used in concurrent chemoradiation therapy (CRT) for treatment of solid tumors [ 3 ]. Although it is clear that platinum drugs and radiation in CRT modalities increase tumor cell killing, improve locoregional control of tumors, and enhance patient survival [ 4 , 5 ], the optimum schedule of the combination and the underlying mechanisms of their synergistic action have not been yet defined [ 6 , 7 ]. Since DNA is the common target of both radiation and platinum chemotherapeutic agents, most studies have focused on the structural and functional alteration of DNA resulting from the combination [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%